Technologies of using of powder materials in casting on consumable patterns - I. G. Sapchenko; S. G. Zhilin; O. N. Komarov (Литьë и металлургия)
Using of powder materials in casting by investment patterns allowed to receive the porous extracting models with high thermal stability, quality of surface, to reduce considerably spoilage of shell forms and to produce founding from metal discards, what considerably reduces the cost of the output goods.